(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
This article aims to explore the Malay conception of philosophy or metaphysics more specifically from the 7th century to the 17th century which spans through the kingdoms of Srivijaya, Malay-Singapore and Aceh with the philosophers’ works of Sakyakirti, Dharmakirti, Kuja Ali (through the narrator of Hikayat Seri Rama) and Hamzah Fansuri, particularly. Philosophy from the various periods of kingdoms refer to the same highest science that is metaphysics which is based on a conception of cause and effect (causality). Philosophers agreed that universe is the created effect from an ultimate cause, but Srivijayan philosophers like Sakyakirti and Dharmakirti from the Yogacara Buddhist school attributed it to the cita, while Kuja Ali and Hikayat Seri Rama from Samkhya Hindu tradition in Malay-Singapore period perceived it as purusa, and Hamzah Fansuri from Islamic Sufism during the Aceh kingdom referred it to Allah SWT. Despite the difference, however, the same approach to self-knowledge has been taken by all philosophers because they believe that the existence of self (consequence) is not different from the existence of the ultimate being (cause); by realising the existence of self, someone will recognise the existence of reality. This similarity and continuity of this concept and its approach throughout the Srivijaya to Aceh kingdom is perhaps the tradition or identity of the Malay philosophy that has not yet been explored and realised by the philosophical community. Makalah ini bertujuan untuk mengupas konsep falsafah atau metafizik Melayu secara khusus dari kurun ke-7 sehingga kurun ke-17 yang menjangkau kerajaan Sriwijaya, Malayu-Singapura dan Aceh dengan karya-karya filsuf Sakyakirti, Dharmakirti, Kuja Ali (melalui narator Hikayat Seri Rama) dan Hamzah Fansuri. Falsafah daripada kerajaankerajaan pelbagai zaman merujuk kepada ilmu tertinggi yang sama iaitu metafizik yang berasaskan konsep sebab dan akibat (causality). Para filsuf bersetuju bahawa alam semesta adalah kesan yang dicipta daripada sebab muktamad, namun ahli falsafah Sriwijaya seperti Sakyakirti dan Dharmakirti dari sekolah Buddha Yogacara mengaitkan perkara ini dengan cita, manakala Kuja Ali dan Hikayat Seri Rama dari tradisi Hindu Samkhya pada zaman Melayu-Singapura menganggap hal ini sebagai purusa, dan Hamzah Fansuri dari tasawuf Islam pada zaman kerajaan Aceh pula merujuknya sebagai Allah SWT. Di sebalik perbezaan itu, pendekatan pengetahuan kendiri yang sama telah diambil oleh semua filsuf kerana mereka mempercayai bahawa “wujud diri” (akibat) adalah tidak berbeza dengan wujud sebab, iaitu dengan menyedari wujud diri, seseorang akan mengenali “wujud hakiki”. Persamaan dan kesinambungan daripada konsep dan pendekatan ini di seluruh kerajaan Sriwijaya sehingga ke Aceh mungkin merupakan tradisi atau jati diri falsafah Melayu yang belum diterokai dan disedari oleh masyarakat falsafah.